Using a portable Raman spectrometer to detect carotenoids of halophilic prokaryotes in synthetic inclusions in NaCl, KCl, and sulfates - Jehlička, Jan; Culka, Adam; Mana, Lilly; Oren, Aharon (Analytical and bioanalytical chemistry, 2018)
Cell suspensions of the haloarchaea Halorubrum sodomense and Halobacterium salinarum and the extremely halophilic bacterium Salinibacter ruber (Bacteroidetes) in saturated solutions of chlorides and sulfates (NaCl, KCl, MgSO4·7H2O, K2SO4, and (NH4)Al(SO4)2·12H2O) were left to evaporate to produce micrometric inclusions in laboratory-grown crystals. Raman spectra of these pinkish inclusions were obtained using a handheld Raman spectrometer with green excitation (532 nm). This portable instrument does not include any microscopic tool. Acceptable Raman spectra of carotenoids were obtained in the range of 200-4000 cm-1. This detection achievement was related to the mode of illumination and collection of scattered light as well as due to resonance Raman enhancement of carotenoid signals under green excitation. The position of diagnostic Raman carotenoid bands corresponds well to those specific carotenoids produced by a given halophile. To our best knowledge, this is the first study of carotenoids included in the laboratory in crystalline chlorides and sulfates, using a miniature portable Raman spectrometer. Graphical abstract ᅟ.
Keywords: Halobacterium salinarum; Spectrum Analysis, Raman; Sodium Chloride; chlorid draselný; Limit of Detection; limita detekce; Bacteroidetes; Carotenoids; karotenoidy; Miniature Raman spectrometer; Halophilic prokaryotes; Salts; chlorid sodný; Inclusions; Potassium Chloride; sírany; Halorubrum; Ramanova spektroskopie; Sulfates